Pengaruh Model Problem Based Learning dalam Meningkatkan Hasil Belajar Siswa SMP Negeri 33 Kota Makassar Kelas IX - Muh. Said; Arismunandar Arismunandar; Muhammad Miftah Fauzan; Imran Eka Saputra (LPPM Universitas Ekasakti Padang, 2023)
This research aims to determine the effect of problem-based learning on improving learning outcomes. This research uses a quantitative approach with a quasi-experimental design to evaluate the impact of implementing a problem-based learning model on Social Sciences (IPS) learning outcomes at SMPN 33 class IX UPT SMP Negeri 33 Makassar City. The research sample consisted of two groups. The sample was determined using purposive sampling, 30 experimental and 30 control class samples. Data was collected using tests. The control group received conventional learning, while the experimental group received learning with a problem-based learning model. Data is collected through test results. The hypothesis test results show a significant difference in the ability of Social Sciences learning outcomes between the two research groups. Confirms that the application of the problem-based learning model has a positive effect in improving social studies learning outcomes at the junior high school level.